(untitled) (Journal of Contemporary Educational Policies and Practices, 2022)
Teachers’ reflection on the teaching-learning process is valuable in stimulating successful lesson delivery and maximize students’ engagement in their learning. In a broader sense, reflective practice is one of the lifelong learning skills, which takes a pivotal role in teacher professional development. However, teachers often encounter challenges in conducting reflective practice activities due to the lack of systemized understanding of reflective practice. Based on that, this paper aims at providing a succinct review of reflective practice in terms of definitions, effectiveness, types, models of reflective practice, and concerns in language teaching through research-based evidence. Furthermore, some suggestions are made for both teachers and educators to encourage varied reflective practice formats, which would promote teacher professional development.